A Novel DIBR 3D Image Watermarking Algorithm Resist to Geometrical Attacks. Issue 6 (1st November 2017) - Wang, Shen; Cui, Chen; Niu, Xiamu
Abstract : A histogram shape based method is utilized to design watermarking algorithm to protect the Depthimage‐based rendering (DIBR) 3D images. To make the watermarking method robust to common attacks, much more suitable pixel groups are selected for watermark embedding which are insensitive to geometric attacks. Taking into account the adjusting of baseline distance in DIBR process might affect the watermarking extraction, a postprocessing is proposed after DIBR process to make the proposed watermarking method much more robust to DIBR process. As the experimental results shown, the proposed method is much more robust to the geometric attacks and combined attacks compared with existing methods. In addition, the proposed watermarking method also has good robustness to the adjusting of baseline distance and depth image blurred.